Implementation of a Sexual Assault Nurse Examiner (SANE) Practitioner Evaluation Toolkit, 2010-2012 Six Sites - Campbell, Rebecca ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. To address the under-reporting and under-prosecution of adult sexual assaults, some communities in the United States implemented the Sexual Assault Nurse Examiner (SANE) Program whereby specially trained nurses provide comprehensive psychological, medical, and forensic services for sexual assault to improve post-assault care for victims and the criminal justice system response. The SANE Practitioner Toolkit was created to teach SANE program staff how to evaluate whether prosecution rates increased in their communities after the implantation of their SAME program. Six SANE programs were selected and provided with comprehensive technical assistance to help them work through the steps in the Toolkit in order to evaluate whether the program was having a beneficial impact on prosecution rates. This study evaluated the effectiveness of the SANE program to increase prosecution rates of sexual assaults through the SANE Practitioner Evaluation Toolkit, and the technical assistance process and resources provided to the sites improved their evaluative abilities.